Shelf life of yogurt taste coffee - Fernandes, Ana Flávia Carvalho; Colpa, Poliana Coste; Paiva, Elisângela Ferreira Furtado; Paiva, Leandro Carlos; Nachtigall, Aline Manke; Vilas Boas, Brígida Monteiro (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to determine the shelf life of yogurt flavored coffee through physical, chemical and microbiological analyzes. During processing of yoghurt, it was proceeded the homogenization of milk and sugar (10%), pasteurization (83ºC for 30 minutes) and cooling until the inoculation temperature (42°C to 45°C). Then, the thermophilic yeast was added. The fermentation was conducted at 45° C for 6 hours, and soon after, stored at a temperature of 4° C and was added by homogenizing the soluble coffee 0.2%. The yoghurt was stored at 4oC for 28 days. Observed linear reduction in pH of yogurt containing 0.2% soluble coffee during storage. The values L*, ho and C* (color analysis) of yoghurt were unchanged during storage, where the respective mean values were 68.11, 88.53 and 14.21. The storage time did not affect the levels of acidity, protein and fat yogurt, were 0.70% lactic acid, 3.76% and 5.2%, respectively. The yogurt containing 0.2% soluble coffee had 2.9 x 107 UFC.mL-1 lactic bacteria. The results of the analyzes of coliforms at 35°C and 45°C, molds and yeast yogurt stored for 28 days are in accordance to the microbiological standards established by legislation for fermented milks. The yogurt containing 0.2% soluble coffee can be stored at 4°C for 28 days, with physical, chemical and microbiological appropriate.